Dual-Band Bandpass Filters Using Stub-Loaded Resonators - Zhang, Xiu Yin; Chen, Jian-Xin; Xue, Quan; Li, Si-Min (IEEE microwave and wireless components letters, 2007)
Dual-band bandpass filters using novel stub-loaded resonators (SLRs) are presented in this letter. Characterized by both theoretical analysis and full-wave simulation, the proposed SLR is found to have the advantage that the even-mode resonant frequencies can be flexibly controlled whereas the odd-mode resonant frequencies are fixed. Based on the proposed SLR, a dual-band filter is implemented with three transmission zeros. To further improve the selectivity, a filter with four transmission zeros on either side of both passbands is designed by introducing spur-line. The measured results validate the proposed design.